PERAN MEDIASI PERSON-ORGANIZATION FIT PADA PENGARUH SUPPORTIVE WORK ENVIRONMENT TERHADAP EMPLOYEE RETENTION - Rini Juni Astuti; Lathifah Nur Baiti (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to analyze the influence of a supportive work environment on employee retention with the mediating role of person-organization fit at XX Yogyakarta Dental Clinic. The type of data used in this research is primary data taken from nurses at the XX Yogyakarta Dental Clinic. The technique used was non-probability sampling with purposive sampling type and with 119 nurses as respondents. The data analysis tool used in this research is the SPSS version 25 application. Data collection uses a questionnaire or Google Form. The method used in this research is multiple linear regression and mediation testing using the Sobel Tes application. The results of this test can be concluded that the Supportive Work Environment has a positive effect on Employee Retention, the Supportive Work Environment has a positive effect on Person-Organization Fit, Person-Organization Fit has a positive effect on Employee Retention and Person-Organization Fit mediates the effect of Supportive Work Environment on Employee Retention. Objectives: 1) Analyze the influence of a supportive work environment on employee retention. 2) Analyze the influence of a supportive work environment on person-organization fit. 3) Analyze the influence of person-organization fit on employee retention. 4) Analyze the influence of person-organization fit which mediates a supportive work environment on employee retention. Methodology: Respondent data was collected using a questionnaire with a total of 20 statement items with 120 respondents. Data processing uses the SPSS version 25 application using classical assumption testing techniques, path analysis and Sobel tests. Research Results: 1) Supportive Work Environment has a positive effect on Employee Retention. 2) Supportive Work Environment has a positive effect on Person-Organization Fit. 3) Person-Organization Fit has a positive influence on Employee Retention. 4) Person-Organization Fit is able to mediate the relationship between Supportive Work Environment and Employee Retention. Research Contribution: Research is expected to provide scientific contributions in the field of human resource management, especially in understanding the positive impact of a supportive work environment, employee retention and person-organization fit. Implications: Able to identify and see the influence of a supportive work environment on employee retention and person-organization fit as a mediating variable. Research limitations: The research locations are spread throughout the Yogyakarta area and there is a possibility that respondents do not understand or have difficulty understanding the statements in the questionnaire so that respondents fill in as they are